Antimicrobial Resistance and Molecular Patterns in Community-acquired Complicated Intra-abdominal Infections: A Multicentric Study - (:unkn) unknown (My University, 2020)
Objective: We aimed to analyze antimicrobial susceptibilities by a molecular evaluation of extended-spectrum beta-lactamase (ESBL) positive of the isolates from communityacquired complicated intra-abdominal infections (CA- IAIs) in Turkey.Method: Clinical samples were obtained during operation. Antimicrobial susceptibilities,inducible beta-lactamase and ESBL status, were determined using Clinical and LaboratoryStandards Institute criteria and interpretive standards. ESBL positive and cefoxitin-resistantisolates were evaluated bla genes for CTX-M, TEM, SHV, PER-1 and plasmidic AmpC familieswith polymerase chain reaction (PCR). We confirmed the results by directly sequencing thebla genes (Macrogen Inc, Korea) with Mega 5.02 and BLAST programs.Results: We isolated 116 pathogens from 81 patients. Clinicians diagnosed 34 (42.1%)patients as acute appendicitis, 15 (18.5%) as cholecystitis, 14 (17.3%) as intra-abdominalabscess, 12 (14.8%) as tumor resection and six (7.3%) acute diverticulitis. Escherichia coli (E.coli) was the most common gram-negative (76%), Enterococcus spp. was the most commongram-positive (13.6%). ESBL production was 12, 3 % in all gram-negative strains; 11, 1%(9/62) in E. coli and 1, 2% (1/9) Klebsiella pneumoniae (K. pneumonia). Quinolone resistance was22.2% and ceftriaxone resistance was 14.5% in E. coli. We detected CTX-M genes in five ofnine ESBL positive isolates. CTX-M-1 group (CTX-M-1, CTX-M-3, and CTX-M-15) was in fourand CTX-M-9 group (CTX-M-14) in one ESBL positive E. coli. One isolate had also AmpC,CMY-2 enzyme (1, 6 %).Conclusion: In our study, ESBL positive gram-negative pathogens were >10%. Quinoloneresistance was >% 20, so that quinolones should not be the first choice for the treatment ofserious IAI's in our country. Cefoxitin resistance was still low in E. coli isolates from CA-IAIs.Regular surveillance data can guide empirical antibiotic therapy in community-acquiredintra-abdominal infections. It should emphasize the importance of sampling for culture tosurgeons for guiding empirical therapy in the future.